Who Decides?: A Review of Challenges of the Discourse around Teaching Excellence - Goode, Claire (Journal of University Teaching and Learning Practice, 2025)
The notion of ‘teaching excellence’ is complex and multi-faceted, and this raises questions around what ‘excellent’ teaching looks like. Similarly, the criteria for teaching excellence awards in different countries and contexts seem to be particularly vague. This paper draws on the existing literature from over thirty years (1992–2024) on the political and organisational discourse around excellence in higher education, the impact of attempting to measure excellence, and how related award schemes recognise teaching excellence. It aims to highlight some of the challenges of this topic, while also encouraging policy makers, leaders, and educational practitioners to reflect on how different terms are used, to consider whose view of excellence is being applied, and to collaborate on a move towards greater clarity around defining and developing excellence in practice.